Psychological Challenges and Coping Strategies Adopted by ICU Nurses during COVID-19 Pandemic in Lahore, Pakistan - Sharoon Sarfraz, Mansoor Ghani, Samina Kausar (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To explore the psychological challenges faced by Intensive Care Unit (ICU) nurses during COVID-19 pandemic and to determine the coping strategies which were used by ICU nurses to combat psychological and emotional stress during the health crisis. Study Design: Qualitative phenomenological approach was used to explore the insights of ICU nurses. Study Subjects: Data were collected from 12 ICU nurses till data saturation. Place and Duration: This study was completed in between August 02, 2021 to January 01, 2022 and was conducted at University of Health Sciences Lahore in collaboration with four tertiary care hospitals of Lahore. Results: Results of this study revealed that the situation was very chaotic. ICU nurses were prone to stress, fear and anxiety because they were more exposed to coronavirus than any other health care professional. The responses of the COVID-19 ICU nurses were categorized into three main themes. Psychological impact of the pandemic in the early stages, social effects of the pandemic and coping strategies. Conclusion: This study concluded that COVID-19 pandemic had a great impact on the psychological well-being of ICU nurses. Despite of adverse conditions, nurses had adopted certain strategies such as family support, religious support and infection prevention protocols which helped them to reduce their stress and fear during the COVID-19 outbreak. Key words: Coronavirus, pandemic, COVID-19 outbreak, psychological experiences, coping strategies, ICU Nurses